2002
DOI: 10.1039/b108640p
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic, infrared, and X-ray absorption studies of adsorption, desorption, and reactions of thiophene on H-ZSM5 and Co/H-ZSM5

Abstract: Temperature programmed desorption and infrared and X-ray absorption near-edge spectroscopies were used during adsorption and reactions of thiophene in order to probe adsorbed intermediates and catalytic structures responsible for thiophene reactions with propane or H 2 on H-ZSM5 and Co/H-ZSM5. Infrared spectra showed that thiophene interacts with acidic OH groups in H-ZSM5 via hydrogen bonding at ambient temperature. No additional bands were detected on Co/H-ZSM5, suggesting the absence of specific interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
47
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 30 publications
3
47
1
1
Order By: Relevance
“…Therefore, zeolites are potential adsorbents for refractory sulfur-containing compounds and have attracted the most interest in recent years. Many publications have reported that zeolites are very effective for the removal of sulfur compounds (Jiang and Ng 2006;Hernandez-Maldonado et al 2004Hernandez-Maldonado and Yang 2003a, 2003b, 2004a, 2004b, 2004c, 2004dVelu et al 2003;Ng et al 2005;Jiang et al 2005, Yang et al 2001, 2003Yu et al 2002;Wang et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, zeolites are potential adsorbents for refractory sulfur-containing compounds and have attracted the most interest in recent years. Many publications have reported that zeolites are very effective for the removal of sulfur compounds (Jiang and Ng 2006;Hernandez-Maldonado et al 2004Hernandez-Maldonado and Yang 2003a, 2003b, 2004a, 2004b, 2004c, 2004dVelu et al 2003;Ng et al 2005;Jiang et al 2005, Yang et al 2001, 2003Yu et al 2002;Wang et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] The observed spectral changes in the nonlinear Raman spectra upon the inclusion of 2-chlorothiophene in the zeolite provide clear evidence for the interaction of the reactant with the catalyst framework, for example, by means of hydrogen bonding (Scheme 1, structure A), which is known to occur at room temperature. [20] In Figure 1 b, a microphotograph of an individual H-ZSM-5 crystal is presented, along with a schematic representation illustrating the crystals intergrowth structure and crystallographic orientations. [27,28] Within the H-ZSM-5 crystals, which have a two-dimensional pore network with interconnected straight and sinusoidal pores, the direction of the straight pores is parallel to the crystallographic b axis.…”
mentioning
confidence: 99%
“…The incorporation of metals such as Cu, Ni, Zn, Ag, Ce and Co [1,2,28,29] oxides such as Al 2 O 3 and TiO 2 [30][31][32][33][34], has received attention in desulfurization by adsorption, because of several possible interactions as much both the aromatic rings as with the heteroatom of sulfur (in the thiophenic derivatives), providing a greater selectivity for the sulfur compounds [35]. For example, the theoretical and experimental study of titanium oxide in the adsorption of thiophene demonstrated relatively weak and selective interactions between thiophene molecules and the metal oxide [36].…”
Section: Introductionmentioning
confidence: 99%